2011
DOI: 10.1021/ma201178j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Novel, Nanocomposite Stannoxane-Based Organic–Inorganic Epoxy Polymers containing Ionic bonds

Abstract: Polymer nanocomposites of epoxies with a novel filler, amino-functional butyltin oxide cage (stannoxane), were prepared and characterized. The nanofiller displays a promising antioxidizing effect, besides mechanical matrix reinforcement. The reinforcement can be assigned to physical interactions among the polymer bonded nanofiller. Moreover, the stannoxane cage undergoes a rearrangement to larger poly amino-functional nano-objects at higher temperatures, which highly reduces its extractability: it is practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 44 publications
6
53
0
Order By: Relevance
“…Nanometer-sized fillers are known to very efficiently reinforce polymeric matrices, due to the high specific surface of the former [44][45][46][47][48][49][50][51]52,53,26]. In their previous work, some of the authors of this paper studied PNIPAm hydrogels reinforced by siloxane-based inorganic nano-phases [54].…”
Section: Introductionmentioning
confidence: 99%
“…Nanometer-sized fillers are known to very efficiently reinforce polymeric matrices, due to the high specific surface of the former [44][45][46][47][48][49][50][51]52,53,26]. In their previous work, some of the authors of this paper studied PNIPAm hydrogels reinforced by siloxane-based inorganic nano-phases [54].…”
Section: Introductionmentioning
confidence: 99%
“…The elastic matrix and the linearly bonding Sn2 cage were chosen for the study of the oxidative crosslinking because of the very strong anti-oxidizing effect found in this system [59] by the authors. Hybrid networks with the following weight loadings of Sn2 were prepared: 0% Sn2 (neat matrix) and 0.05e100 mol% Sn2 (^0.1e40 wt%, see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…the procedure published in Ref. [64], using the molten and supercooled epoxide DGEBA, the liquid Jeffamine D2000 and a 50 wt% stannoxane "Sn2" cage solution in toluene. (This solvent was removed just after gelation of the reaction mixture, it served to ensure good compatibility in the early stages of the reaction blending of the epoxide with Sn2).…”
Section: Synthesis Of the Hybrid Epoxiesmentioning
confidence: 99%
See 2 more Smart Citations